If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 6 = 4x + 9 Reorder the terms: 6 + 2x = 4x + 9 Reorder the terms: 6 + 2x = 9 + 4x Solving 6 + 2x = 9 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 6 + 2x + -4x = 9 + 4x + -4x Combine like terms: 2x + -4x = -2x 6 + -2x = 9 + 4x + -4x Combine like terms: 4x + -4x = 0 6 + -2x = 9 + 0 6 + -2x = 9 Add '-6' to each side of the equation. 6 + -6 + -2x = 9 + -6 Combine like terms: 6 + -6 = 0 0 + -2x = 9 + -6 -2x = 9 + -6 Combine like terms: 9 + -6 = 3 -2x = 3 Divide each side by '-2'. x = -1.5 Simplifying x = -1.5
| 5y-8-y=1 | | 2x+6=4+9 | | 5x=x+t | | 9X+5Y=-56 | | X+xy+y=21 | | 3x+8=-4+71 | | 7=-3-4b | | 5u+5(1-6)=u+8 | | 5x-3=6x+2x-9 | | 2cos^2(x)-sin(x)=0 | | 4*ln(x)-x=6 | | -3+6=2x-9 | | X^5/3=0.5 | | 10x-7(3)=-18 | | 17a-4= | | 4(3x-8)=28 | | 16y-10=14 | | 1/3(6x=2x | | 8x+8=3x+73 | | 3ln(2x+1)-5=1 | | (3x-x)+(8x+9)= | | x^3-2x^2+36=0 | | 4(5x-8)-13x=24 | | (12y*12y-144)=(3y*3y) | | x^2+(6x+17)=0 | | n+6-2=1 | | 2+c-3=3 | | X^4-3x^2+4x-6=0 | | F(x)=-3x+5 | | (cd+2)+cd-4= | | x^2-(m+1)x-5=0 | | (8x+4)=(5x+2) |